Synthesis and characterisation of alumino-silicate-fluoride based glass ceramics from clam shell and soda lime silica glass waste - Abdul Rahman, Nadia Asyikin (2019)
The design of bioactive glass materials which is strictly related to glass technology is one of the main achievements in glass production. The attention towards the preparation of glass and glass-ceramics materials for applications in dentistry has increased. The CaO-SiO2-CaF2-P2O5-Al2O3 glass system has been studied by other researchers where the material produced has high mechanical strength as compared to other bioactive glass and glass-ceramics. Although this glass and glass-ceramics are well established for dental application, its effect on using waste materials such as clam shell (CS) and soda lime silica (SLS) glass for use in the dental field has not been extensively studied. Thus, in this study, Alumino-Silicate-Fluoride (ASF) glass and glass- ceramics were fabricated and synthesised using CS and SLS glass as a source of CaO and SiO2, respectively. A series of ASF glass samples were prepared by using the conventional melt-quench technique. The thermal, chemical, physical, structural and mechanical properties of precursor glass and glass-ceramics were measured by differential scanning calorimetry (DSC), x-ray fluorescence (XRF), energy-dispersive x-ray (EDX), average density, molar volume, linear shrinkage, x-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) and Vickers hardness (Hv) measurement. The density of the un-sintered pellets was found to increase with increasing of CS powder in the glass samples. Moreover, the density and linear shrinkage of glass-ceramic samples also increased with the increasing of sintering temperature. However, these measurements have slightly decreased at 1100 ℃ and 1200 ℃. The introduction of CaO-SiO2-CaF2-P2O5-Al2O3 containing materials, as well as the specific regime of sintering of the glass, gave glass-ceramics materials with crystalline phases of the hexagonal Ca5(PO4)3F (fluorapatite), orthorhombic Al5SiO9.5 (mullite) and anorthic (Ca(Al2Si2O8)) (anorthite) crystals. The average calculated crystallite size of fluorapatite obtained from XRD was found to be in the range 16-53 nm. The formation of needle-like microstructure, which is known as fluorapatite, was observed in FESEM micrograph. The appearance of P−O and Si−O−Al bands detected from FTIR measurements indicate that the formation of apatite and mullite crystal phases. The Hv of the glass-ceramic have the same trends as the density of the pellets. The results obtained shows that there was a slight decrease in both measurements at 1100 ℃ and 1200 ℃, due to porosity formation and decomposition of fluorapatite phase into mullite and anorthite phase. As a result, the optimum density and Hv were in a range of 2.651-2.810 g/cm³ and 4.75-6.14 GPa, respectively, at 1000 ℃. Overall results promoted the ASF glass and glass- ceramics samples produced from waste materials as a high potential candidate for dental applications since both fluorapatite and mullite phases are likely to result in the development of glass-ceramics with high mechanical strength.